Die Wunden des Staates Kriegsopfer und Sozialstaat in Österreich nach dem Ersten Weltkrieg (1914-1938) - Pawlowsky, Verena (2015)
The study's subject is the assistance for the victims of World War I in Austria. It explains the numerous measures taken in favour of disabled veterans and war widows during the war and in the post-war period and describes the powerful organisations of the invalids. The assistance for war victims expressed very early social policy as supported by the state.